The study of go-kart assembly / Muhamad Airul Azli Kamarudin, Ridzuan Ismail and Mohd Sani Soid - Kamarudin, Muhamad Airul Azli; Ismail, Ridzuan; Soid, Mohd Sani (2002)
The study of the go-kart assembly is not only focus on the assemble only, its also cludes many aspect on the go-kart like economic, factor, advantages and problem that volve in go-kart manufacturing field nowadays. This is a kind of very limited source of vision of study is important for the study of the go-kart itself.